THE EFFECTS OF CHITOSAN APPLICATION AGAINST ALUMINUM TOXICITY IN WHEAT (Triticum aestivum L.) ROOTS - Kurtuluş, G.; Vardar, F. (Annali di Botanica, 2021)
Aluminum (Al) is the most common metallic element after oxygen and silicon, which makes up 8.1% of the earth's crust. If the acidity of the soil increases due to several environmental factors, Al is dissolved and transformed into a toxic form. In acidic soils, dissolved Al, usually present in concentrations ranging from 10 to 100 µM, is an important factor in inhibiting growth for plants. In the present study, we aimed to alleviate the Al toxicity by chitosan (CHT) application in wheat. Wheat (Triticum aestivum L.) seeds germinated for 96 h in different solutions. Distilled water was used as control. Toxicity was established using 100 µM AlCl3 solution (pH 4.5). Roots were treated with 0.1, 0.25 and 0.5 mg/L CHT solutions to alleviate toxicity. Based on our results, while Al inhibited the elongation of wheat roots, an increase in root elongation was observed as a result of the CHT application. Al-induced lipid peroxidation, loss of membrane integrity, proline deposition, and antioxidant enzyme activities. The Al-damage was improved by CHT and Al-resistance rose with increasing antioxidant enzyme activity. As a result, the alleviation effects of CHT on Al-induced stress symptoms were found to be higher in lower concentrations (0.1 and 0.25 mg/L).